Ð˜Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ ÑÐ½Ð° Ð¿Ð¾ÑÐ»Ðµ Ð¿Ð¾ÑÑ‚Ð¾ÑÐ½Ð½Ð¾Ð³Ð¾ Ð¸ Ñ€Ð¸Ñ‚Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ñ‹Ñ… Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ð¹ - Ventskovska, O. A.; Shylo, O. V.; Babiychuk, G. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
Even small fluctuations in ambient temperature, in addition to the initiation of thermoregulatory response of the organism, lead to changes in sleep-wake cycle. It is shown that long-term cold exposure (LTCE) and rhythmic cold exposures (RCE) cause changes in the sleep depth and duration: after LTCE both slow wave sleep (SWS) and rapid eye movement (REM) sleep are increased in the duration; after RCE (â€“12Â°C) only the REM sleep duration is significantly increased; after RCE (+10Â°C) the SWS duration is increased in light period. Revealed sleep amount increase in dark period in animals after LTCE and RCE (â€“12Â°C) after transfering them into normal environmental conditions, is probably due to intention of an organism to reduce the thermal load. Changes in SWS under RCE (+10Â°C) after each 15 minutes of cold exposure are probably related to skin temperature changes. It is believed that skin temperature change is even more powerful factor for the sleep initiation than change in the body â€œcoreâ€ temperature. These adaptive changes in sleep are agreed with the hypothesis about a high need in sleep as a physiological mechanism for the periodic significant reduction of energy expenditure which is increased during acclimation.